Sharia-Based Society Empowering Technopreneur for Santri Ponpes AlMisbah Ciseeng Bogor - Sufyati HS; Tri Siswantini; Anggi Angga Resti; Hammas Hubaibi Akbar El Hamid; Akhdanaila Hikmah Wirawan (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Islamic boarding schools are Islamic-based educational institutions that play a substantial role in educating students holistically. However, economic and technological challenges often become obstacles in empowering students to become Sharia-based technology entrepreneurs. In producing quality student graduates, a curriculum is needed that is not only spiritually based education but must also be relevant to today's world of work. Through the application of Sharia technopreneur, an entrepreneurship curriculum utilizing Sharia-based technology can be carried out to produce quality student qualifications. This activity aims to provide education, socialization, and support for Sharia entrepreneurship knowledge, identification of halal products/halal certification, and how to market products using digital technology (digital marketing), as well as digital payments according to Sharia principles. The event was held at Al-Misbah Islamic Boarding School, Ciseeng, Bogor, West Java. The implementation method is explanation, practical training, and mentoring, giving questionnaires before and after (pre-test and post-test) PKM activities. The results of this activity show an increase in students' knowledge of each sub-material provided based on the pre-test and post-test. This program has significant implications for economic and technological empowerment in the dormitory environment. Apart from improving students' technological skills and knowledge, this activity also opens up opportunities for Sharia-based economic development in the surrounding community. It needs to be implemented sustainably by collaborating between academics, Islamic boarding schools, and the industrial world to increase the financial independence of the people.